CORRELATION BETWEEN SELF-EFFICACY AND THE LISTENING COMPREHENSION OF THE EIGHTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP-UR - Rizka Amelia Isty; Fadly Azhar; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This correlational research is aimed to find out whether there is a significant correlation between self-efficacy and the listening comprehension of the eighth semester students of English Study Program FKIP-UR. The sample was 35 students selected through purposive sampling technique. The instruments used in this research were the questionnaire on self-efficacy and the documentation of the students’ TOEFL listening comprehension score provided by the Language Centre of Universitas Riau. The research findings revealed that the self-efficacy of the eighth semester students of English Study Program FKIP-UR was at the average level (180.60), and their listening comprehension was at the mediocre level (49.83). The cross tabulation analysis showed that the students who had higher self-efficacy had a high tendency to have better listening comprehension score level. Based on Pearson correlation analysis, it was obtained that the correlation coefficient between students’ self-efficacy and the listening comprehension was 0.786 with the Sig. value=0.00. Hence, it could be concluded that there was a significant correlation between self-efficacy and the listening comprehension of the eighth semester students of English Study Program FKIP-UR. The interpretation of the correlation coefficient showed that there was a strong positive correlation between both variables. As a consequence, the null hypothesis was rejected.Key Words: Correlation, Self-efficacy, Listening Comprehension